FRAMING THE NEWS OF DONALD TRUMP SHOOTING IN PENNSYLVANIA ON CNN AND BBC MEDIA - Rihaadatul 'Aisy AlQodri; Abdul Basid (LLDIKTI Wilayah X, 2024)
This research aims to (1) analyze how the two major media, CNN and BBC, framed the issue and presented information about the news of “The Shooting of Former President of the United States, Donald Trump on July 13, 2024, in Pennsylvania” based on Robert M. Entman's perspective; (2) explain the differences between the two media in conveying information; (3) explain the impact of framing on society. This research is descriptive qualitative research. The analysis in this study uses Robert M. Entman's framing analysis theory. The results of this study are: (1) the media in framing an issue through the process of selection and highlighting issues, so that there is a reduction or disposal of certain facts through the selection process and accentuates certain facts to the consumer audience; (2) in the frame of the two CNN and BBC news uploaded on July 14, 2024 regarding the shooting of Donald Trump at his political rally in Pennsylvania, there are differences in the highlighting of issues; (3) as for the impact of framing on people's perspectives is the construction of consumer audiences' understanding of an issue based on the frame built by the media.